Spectroscopy of a tetrahedral doubly magic candidate nucleus 70160Yb90. (8th March 2019) - Saha, A; Bhattacharjee, T; Curien, D; Dudek, J; Dedes, I; Mazurek, K; Góźdź, A; Tagami, S; Shimizu, Y R; Banerjee, S R; Rajbanshi, S; Bisoi, A; et al.
Abstract: The decay scheme of 160 Yb nucleus populated in the 148 Sm( 16 O, 4n) 160 Yb reaction at 90 MeV has been studied. The gamma-coincidence data have been collected by using Indian National Gamma Array (INGA) composed of twenty Compton-suppressed Clover-germanium detectors. Compared to the prior publications, the level scheme has been significantly modified owing to the observation of triple γ -coincidences and the measurements of γ intensities, R θ (asymmetry ratio), directional correlation of oriented states and integrated polarisation directional correlation of oriented states ratios. Theoretical results relevant for the exotic shape-coexistence related to the present context are presented and discussed. They illustrate the consequences of the fact that 160 Yb is expected to be a doubly-magic ( Z  = 70 and N  = 90) tetrahedral-symmetry nucleus as predicted by other authors. The historical criteria of identification of such a symmetry in nuclei are critically revisited in the context of the actual measurement and interpretation of its results and the precise new criteria are formulated employing recent results of the Fukuoka-Strasbourg collaboration. The experimental results are interpreted and discussed in detail. Limiting values of branching ratios for transitions observed by other authors but unseen in the present work are estimated. The population criteria of the β and γ vibration bands are revisited and discussed. Although no indication of the presence of the stable tetrahedral configuration has been obtained, arguments are given towards the possible presence of the Y 32 ('tetrahedral component') vibrations around the ground-state equilibrium. With the improvement of the spectroscopic information provided by the new data the way is opened for designed experiment(s) based on the unambiguous identification criteria of tetrahedral symmetry presented in this article.